Education and growth in Malaysian knowledge-based economy - Tan, Hui Boon; Wong, Mei Foong; Mohd Noor, Zaleha (Faculty of Economics and Management, Universiti Putra Malaysia, 2006)
The Malaysian economy of today is in the process of evolving from a production-based economy (P-economy) into a knowledge-based economy (K-economy). In the theory of K-economy, knowledge is recognized as one of the primary factors in sustaining economic growth aside from land, labor and physical capital. In this study, we focus on formal education as a knowledge-based input in the Malaysian production function. 'The multivariate cointegration test result indicates that education, technical progress, labor, capital and economic growth of the country have a long-run equilibrium relationship, which allows them to elevate together over time. Even though several previous studies show that education might not contribute significantly to the growth of developing countries, our short-run estimated results, based on vector error-correction modeling, show that human capital, with the stock of knowledge accumulated through education, does contribute to Malaysian economic growth. In fact it can be considered as, based on the estimated production elasticities, the second most important input factor, alter physical capital, that promotes economic growth. This result provides empirical evidence that education, which is causally linked to the physical capital and technological progress, is an important mechanism to escalate the transformation of Malaysia into a fully-developed K-economy.